Exploring the effects of packaging on consumer experience and purchase behaviour: insights from eye tracking and facial expressions on orange juice - Mehta A; Serventi L; Kumar L; Torrico DD (John Wiley & Sons Ltd on behalf of Institute of Food, Science and Technology (IFSTTF), 2023)
Packaging is crucial in attracting consumer attention, conveying product identity, influencing product perception and affecting approach-based consumer behaviours. The present exploratory study aimed to gain insights into the effects of packaging on consumer experiences and the factors driving willingness to buy different orange juice products based on packaging. Eye tracking and facial expressions were used to capture the consumer perception journey, from the initial interaction to the final product evaluation. The study also examined hedonic liking, explicit emotions and different label attributes in the evaluation stage, and the importance of texture, price and the New Zealand (NZ)-made logo in the validation stage. Results showed that the packaging's physical features significantly affected consumer's attention during the initial interaction stage. Implicit emotions provided deeper insights into consumers' preferences in the orientation stage. Nutritional information gained maximum visual attention (fixation counts = 0.40) in the evaluation stage, while the NZ-made logo (odds ratio = 15.62) drove purchase intention. The study revealed that the packaging that attracted the maximum attention was not necessarily the one with the highest liking score. Moreover, consumers may not pay much visual attention to attributes (price, r = −0.22) that they reported to be important. By advancing our knowledge in this field, marketers and product designers can refine their strategies and create packaging that captures visual attention and evokes positive emotional responses, ultimately influencing consumer behaviours
Keywords: Emotions; facial expressions; hedonic liking; packaging type; visual attention; willingness to buy